Determination of the correlates of risk of developing eating disorders based on exercise motivation, anthropometric and demographic characteristics - Hon, Tan Jing (2021)
Disordered eating is a cluster of unhealthy eating habits and weight behaviors, with a negative impact on psychological and physical health. The aim of this study was to explore the prevalence of eating disorders and their risk factors, including anthropometric characteristics, exercise motivation and behaviours among young adults in Malaysia. An online survey was conducted involving 150 participants aged 18 to 35 years, who were randomly recruited through snowball and convenience sampling techniques. The Behavioral Regulation Exercise Questionnaire -3 (BREQ-3), Compulsive Exercise Test (CET), Compensatory Unhealthy Eating Scale (CUES) and Eating Attitudes Test (EAT-26) were administered to determine participants’ exercise motivations, likelihood of compulsive exercise, compensatory eating, as well as the prevalence of disordered eating respectively. Using Structural Modelling Equation analysis, with gender and BMI status as moderators, the results revealed adequate model fit. Specifically, exercise motivation positively predicts compulsive exercise, subsequently predicts risks of eating disorders. The results also implicated that autonomous motivation negatively predicts compensatory eating in individuals who were overweight or obese. Among males, compulsive exercise positively predicts compensatory eating, and subsequently predict the risks of developing eating disorders. Compulsive exercise positively predicts the risk of developing eating disorders in individuals with normal weight and positively predicts compensatory eating in overweight/obese. In short, young adults’ gender and their BMI statuses seem to differ on some of the risk factors of developing eating disorders. The findings of the current study call for increased awareness, understanding of eating disorders and related risk factors among young adults in Malaysia. In the field of clinical psychology, clinicians are encouraged to consider patients’ gender and BMI statuses as well as to conduct thorough assessments of clinical variables including exercise beliefs and motivation, compensatory eating behaviors to examine the possibility of exercising for unhealthy reasons and the risk of developing eating disorders.